Paul Ricoeur's anthropology of forgiveness - Dionisio, Guillermo R. (2016)
In his philosophical anthropology Paul Ricoeur sees man's innate goodness, despite his prosperity for evil, ramifying into many capacities among them, forgiveness. The capacity to forgiveness. The capacity to forgive, for Ricoeur, lies between the paralysis of the power to act due to human fault, and the possible liftingof this incapacity through the separation of the offending agent from his or her evil deeds. But if forgiveness obtains in isolating offenders from their evil deeds, their self-understanding, sense of responsibility, and identity might become distorted and inaccurate, and would make us question whether forgiveness should be horizontal, that is, conditional; or vertical, that is, unconditional. This article aims to address these problems using Ricoeur's narrative approach to understanding the self and his idea of forgiveness that intersects with justice and gift.
Keywords: Philosophical anthropology; Forgiveness